2001
DOI: 10.1105/tpc.010114
|View full text |Cite
|
Sign up to set email alerts
|

A 90-kD Phospholipase D from Tobacco Binds to Microtubules and the Plasma Membrane

Abstract: The organization of microtubule arrays in the plant cell cortex involves interactions with the plasma membrane, presumably through protein bridges. We have used immunochemistry and monoclonal antibody 6G5 against a candidate bridge protein, a 90-kD tubulin binding protein (p90) from tobacco BY-2 membranes, to characterize the protein and isolate the corresponding gene. Screening an Arabidopsis cDNA expression library with the antibody 6G5 produced a partial clone encoding phospholipase D (PLD), and a full-leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(112 citation statements)
references
References 87 publications
(82 reference statements)
7
102
0
3
Order By: Relevance
“…In mammalian systems, PLD activity was found to be modulated by both tubulin (Chae et al 2005) and actin (Kusner et al 2002;Lee et al 2001). Similar observations have been made in plants, with PLD interacting with elements of the cytoskeleton as well as other organelles (Gardiner et al 2001(Gardiner et al , 2003Andreeva et al 2009;Ho et al 2009). PLD and PLC signalling pathways are known to overlap and in some cases directly interact with each other, for example, after stimuli such as phosphate deprivation, pathogen attack and cadmiuminduced cell death (Profotova et al 2006;Yakimova et al 2006;Russo et al 2007).…”
Section: Introductionsupporting
confidence: 63%
“…In mammalian systems, PLD activity was found to be modulated by both tubulin (Chae et al 2005) and actin (Kusner et al 2002;Lee et al 2001). Similar observations have been made in plants, with PLD interacting with elements of the cytoskeleton as well as other organelles (Gardiner et al 2001(Gardiner et al , 2003Andreeva et al 2009;Ho et al 2009). PLD and PLC signalling pathways are known to overlap and in some cases directly interact with each other, for example, after stimuli such as phosphate deprivation, pathogen attack and cadmiuminduced cell death (Profotova et al 2006;Yakimova et al 2006;Russo et al 2007).…”
Section: Introductionsupporting
confidence: 63%
“…PLD is one plasma membrane protein that may be responsible for linking cortical microtubules to the plasma membrane (Gardiner et al 2001;Dhonukshe et al 2003;Drøbak et al 2004;Hong et al 2008) and is therefore suggested to act as a structural and signaling link between the plasma membrane and the cytoskeleton in tobacco and in Arabidopsis (Gardiner et al 2003). The overexpression of a member of PLD family has been shown to lead to enhanced FT (Li et al 2004).…”
Section: Cold Signal Perceptionmentioning
confidence: 96%
“…PLD controls cytoskeleton stability and linkage to the plasma membrane in a Ca 2? -dependent and stressactivated manner (Gardiner et al 2001;Dhonukshe et al 2003).…”
Section: Cold Signal Perceptionmentioning
confidence: 99%
“…Pacheco et al (2007) demonstrated that microtubule-active drugs (colchicine and taxol) inhibited lipid body biogenesis elicited by immune response to infection in monocyte of mouse. This correlation between microtubules and lipid bodies seemed plausible on the basis of the information that phospholipase D cosediments together with microtubules (Gardiner et al 2001;2003;Dhonukshe et al 2003) and phospholipase PLD1 regulates the formation of cytosol lipids (Andersson et al 2006). On the other hand, it has also been suggested that microtubules through dynein are involved in the fusion of the small lipid bodies into the big ones, since the destruction of microtubules with nocodasol inhibits this process (Boström et al 2005).…”
Section: Discussionmentioning
confidence: 96%